Analysis Of Child Labour Practices In Urban And Rural Communities In Cross River State, Nigeria - Odey, Stephen Adi; Sambe, Ngutor (Advances in Social Sciences Research Journal, 2018)
The study was aimed at identifying child labour practices existing in urban and rural areas in Cross River state. The study utilized survey design while cluster random sampling and purposive sampling technique was used to select samples, questionnaires and key informant interview were deployed for data collection. The analysis of data involved use of percentages and transcription of views of the key informants. The study discovered that child labour practices in urban areas of Cross River state include domestic work, street hawking, and shop/store operating, blue-collar laboring, plate washing in restaurants, car washing and bus conducting. In rural communities, child labour the practices are kiosk operating, palm wine tapping and sales. The findings have also shown that in urban communities, nearly half of the respondents are paid for their services while in rural areas most of the children are not paid for their services. The amount of money paid to the child labourers in the urban areas ranges mostly between <s>N300-<s>N500 while in the rural communities, majority of respondents receive below <s>N200. The category of people engaging children as child labourers in urban areas, are mostly business owners/operators while in rural areas, parents are the group that uses children as child labourers the most. Recommendations for controlling child labour in urban areas include execution of child right laws, creation of awareness and prosecution of people who engage children in labourous practices. In rural areas, creation of awareness, poverty reduction and execution of child right laws was recommended.</s></s></s> <s><s><s> </s></s></s>